Susceptibilidade aos antibióticos e aos biocidas clorexidina e cloreto de benzalcônio em isolados clínicos de Acinetobacter baumannii - Évora, Bruna Helena Silva Rendall (2019)
Acinetobacter baumannii species stands the main pathogens involved in hospital-acquired infection (HAI) in hospitalized patients, particularly in Intensive Care Units (ICUs), and has a great capacity to acquire antimicrobial resistance mechanisms. Recently, the reduction of susceptibility to biocides as antiseptics and disinfectants has been reported in many species, including A. baumannii. The aim of the present study was to determine the susceptibility profile to antibiotics and to the biocides chlorhexidine and benzalkonium chloride susceptibility profile of clinical isolates of A. baumannii from general hospitals in the city of Natal, Rio Grande do Norte, Brazil. The samples were collected among March 2013 to March 2014, identified through conventional biochemical tests, confirmed by the blaOXA-51 gene and MALDI-TOF system, and stored in a freezer at -20 ° C in the Laboratório de Bacteriologia Médica (LaBMed), UFRN. The susceptibility of 135 samples of A. baumannii to antibiotics commonly used in clinical practice was evaluated by the disc diffusion method (kirby-bauer) and by EDTA (ethylenediaminetetraacetic acid) combined disk test. The susceptibility to biocides was evaluated by determination of the Minimum Inhibitory Concentration (MIC) by using the broth microdilution method, according to CLSI recommendations. In addition, the Polymerase Chain Reaction (PCR) assay was used for the detection of genes encoding the carbapenemases IMP-1, VIM-1, NDM-1, and OXA-23, 24, 58, 143 and the efflux pumps QacE, AdeB and AdeJ. The multidrug resistance (MDR) profile was observed in 70,37% (95/135) of the isolates and 44,21% (42/95) were extensively resistant (XDR) since they were resistant to all antibiotics, except for Tigecycline, whose resistance was observed in only one isolate. Resistance to carbapenems was detected in 71.85% (97/135) of the isolates. Seventy seven isolates were positive for metallo-betalactamases (MBLs) and just the NDM-1 and IMP-1 enzymes were detected in 15,85% and 2,06% on these isolates, respectively. The blaOXA-23 (90%) and blaOXA-143 (28%) genes were the most prevalent. Regarding the biocides susceptibility assessment, 19,25% (26/135) isolates presented reduced sensitivity to chlorhexidine and 40% (54/135) to benzalkonium chloride. The adeB and adeJ genes were detected in almost all isolates corresponding to 115 (85.19%) and 129 (95.85%), respectively, although this results did not show a positive association with tolerance to the biocides tested, statistically (p<0,05). However, qacE gene showed a significant relationship (p=0, 0006) with the susceptibility reduced to chlorhexidine, being present in 46,15% (12/26) of the isolates less susceptible to this compound. Another significant association was observed between the reductions of susceptibility to benzalkonium chloride and the multirresistance profile of the isolates. This research describes strains of A. baumannii with a resistance profile that greatly compromises the treatment of infections by this microorganism, as well as limits the agents used in the hospital sanitization and disinfection process. There should therefore be permanent surveillance of cross-transmission in hospital settings and seek the use of more effective biocides.